Venous Air Microembolism in Chest CT Angiography: Evidence of Normalization of Deviance Phenomenon - Silva, Claudio; Leal, Ema (Indian Journal of Radiology and Imaging, 2021)
Purpose This article provides evidence that detection of venous air microbubbles (VAMB) in chest computed tomography angiography (CTA) can be an indicator for “normalization of deviance” phenomenon in CT.Method and Materials Institutional review board-approved retrospective study, with waiver for informed consent. Contrast-enhanced chest CT performed during 6 months were reviewed for presence of VAMB in venous segments visible in chest CT (subclavian, brachiocephalic vein, superior vena cava) and cardiac chambers. VAMB volumes were quantified through a semiautomatic method (MIAlite plugin for OsiriX), using a region of interest (ROI) covering the bubble. With basal results, protocols for correct injection technique were reinforced, and VAMB were estimated again at 1 and 3 months. Six months later, questionnaires were sent to the CT technologists to inquire about their perception of VAMB. Descriptive measures with central distribution and dispersion were performed; statistical significance was considered at p < 0.05.Results A total of 602 chest CTA were analyzed, 332 were women (55.14%), with a median age of 58 (interquartile range [IQR] 44–72) years. Among those, 16.11% (100 cases) presented VAMB. Most were emergency department patients (51.6%), male (50.3%), with a median age of 54 (IQR 26) years. There was no difference on detection of VAMB regarding sex (p = 0.19), age (p = 0.46), or referral diagnosis (p = 0.35). Mean air bubbles volume was 0.2 mL (range 0.01–3.4 mL). After intervention, the number of exams with VAMB dropped to 3.29 % (3/91) (p < 0.001). On the 6-month query, 50% of the technicians still considered that VMAB is inevitable, and 60% thought that the occurrence is not associated to risk, and therefore, not actionable.Conclusion VAMB are a frequent finding in chest CTA, and being independent from patient-related variables, it is likely due to technical issues such as intravenous access manipulation during the exam. Reduction after reinforcement of proper performance, and certification of a low concern from CT technicians for any risk associated, provides evidence that there is normalization of deviance in this everyday procedure.
Keywords: air bubbles; air embolism; computed tomography angiography; normalization of deviance